2018
DOI: 10.1155/2018/4868412
|View full text |Cite
|
Sign up to set email alerts
|

Royal Jelly Supplementation Improves Menopausal Symptoms Such as Backache, Low Back Pain, and Anxiety in Postmenopausal Japanese Women

Abstract: Objectives This study aimed to evaluate the effect of Royal Jelly (RJ) at a dose of 800 mg/day on menopausal symptoms in healthy Japanese postmenopausal women with placebo-controlled design. Material and Methods A total of 42 healthy Japanese postmenopausal women have been recruited for this study. The subjects were randomized to oral treatment with either 800 mg of protease-digested lyophilized powder of RJ (enzyme-treated RJ) or placebo (800 mg of dextrin) daily for 12 weeks. The level of menopausal symptoms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 20 publications
0
20
0
2
Order By: Relevance
“…It is the specic food for the queen honey bee throughout her life period and it is involved in the fertility and longevity of the queen. 1 A multitude of pharmacological activities have been reported in experimental animals [2][3][4][5][6] and in clinical trials, [7][8][9][10] including antitumor, 2 anti-oxidant, 3 anti-inammatory, 4 antibacterial, 5 and anti-aging, 6 improvement of chills, 7 neck muscle strain, 8 tinnitus, 9 female menopausal symptoms, 10 age associated muscle strength decline, 11 and lipoprotein metabolism by lowering serum total cholesterol and leading to low-density lipoprotein levels, as well. 12 The chemical composition of RJ consists of: water (60-70%), proteins (9-18%), sugars (7.5-23%), lipids (3-8%), and other trace compounds.…”
Section: Introductionmentioning
confidence: 99%
“…It is the specic food for the queen honey bee throughout her life period and it is involved in the fertility and longevity of the queen. 1 A multitude of pharmacological activities have been reported in experimental animals [2][3][4][5][6] and in clinical trials, [7][8][9][10] including antitumor, 2 anti-oxidant, 3 anti-inammatory, 4 antibacterial, 5 and anti-aging, 6 improvement of chills, 7 neck muscle strain, 8 tinnitus, 9 female menopausal symptoms, 10 age associated muscle strength decline, 11 and lipoprotein metabolism by lowering serum total cholesterol and leading to low-density lipoprotein levels, as well. 12 The chemical composition of RJ consists of: water (60-70%), proteins (9-18%), sugars (7.5-23%), lipids (3-8%), and other trace compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, menopausal women may receive hormone therapy to alleviate discomfort and lower their risk for various serious diseases such as osteoporosis and cardiovascular disorders. However, hormone therapy is associated with increased risk of cancer [92,93]. Several natural alternatives (including RJ) have been under investigation as safer alternatives.…”
Section: Rj Might Enhance Longevity In Humans By Promoting Generalmentioning
confidence: 99%
“…Cell culture models revealed that the role of RJ in bone formation is due to upregulation of procollagen I α1 gene expression [96,97], enhancement of intestinal calcium absorption, and increased bone calcium content [95]. Human studies lend further support to this evidence; pRJ at a dose of 800 mg/day significantly decreased lower back pain in healthy menopausal women [93]. Likewise, daily consumption of 150 mg of RJ for three months exerted cardioprotective effects by improving lipid profile of postmenopausal women [92].…”
Section: Rj Might Enhance Longevity In Humans By Promoting Generalmentioning
confidence: 99%
See 1 more Smart Citation
“…During menopause, sudden estrogen level withdrawal affects the autonomic nervous system, leading to the development of neurodegenerative diseases (e.g., Alzheimer disease), mood disorders (e.g., anxiety, depression) or headache, low back pain or backache. 42 postmenopausal women accusing anxiety, backache and low back pain were recruited and randomly received either 800 mg of dextrin or 800 mg of enzyme-treated royal jelly, for 3 months [ 52 ]. After this period, both anxiety score and backache score in royal jelly group were significantly decreased compared to placebo group.…”
Section: Studies Of Royal Jelly As a Beneficial Therapeutic Agent mentioning
confidence: 99%